Less or more hemodynamic monitoring in critically ill patients. Issue 4 (August 2018) - Jozwiak, Mathieu; Monnet, Xavier; Teboul, Jean-Louis
Abstract : Purpose of review: Hemodynamic investigations are required in patients with shock to identify the type of shock, to select the most appropriate treatments and to assess the patient's response to the selected therapy. We discuss how to select the most appropriate hemodynamic monitoring techniques in patients with shock as well as the future of hemodynamic monitoring. Recent findings: Over the last decades, the hemodynamic monitoring techniques have evolved from intermittent toward continuous and real-time measurements and from invasive toward less-invasive approaches. In patients with shock, current guidelines recommend the echocardiography as the preferred modality for the initial hemodynamic evaluation. In patients with shock nonresponsive to initial therapy and/or in the most complex patients, it is recommended to monitor the cardiac output and to use advanced hemodynamic monitoring techniques. They also provide other useful variables that are useful for managing the most complex cases. Uncalibrated and noninvasive cardiac output monitors are not reliable enough in the intensive care setting. Summary: The use of echocardiography should be initially encouraged in patients with shock to identify the type of shock and to select the most appropriate therapy. The use of more invasive hemodynamic monitoring techniques should be discussed on an individualized basis.